Caracterización de las prácticas ancestrales agrícolas vigentes en la parroquia Columbe y su impacto en la calidad de la producción - Sagñay Guacho, Felix Geovanny (2025)
In this research project, the ancestral agricultural practices applied in the Columbe parish were characterized. This allows us to establish the most efficient practices while maintaining and improving the quality of the product, potentiating the production achieved and offering a promising future for these traditional methods. Thus, to develop this research work, it is proposed to carry out quantitative-qualitative, field, nonexperimental research using tools such as surveys, interviews, NTE INEN standards for agricultural practices, technical sheets, and finally, a process manual. This has allowed us to collect data for later analysis, interpretation, and evaluation of the consequences. The results obtained have shown us the ancestral practices that are still applied today. However, there have been changes due to the technical and technological advances that exist today, highlighting the urgent need for the application of new techniques to avoid losses mainly in the storage stage. Finally, the aforementioned activities require new activities, such as implementing modern storage techniques and maintaining hygiene standards, that avoid cross-contamination due to the application of ancestral techniques that have been passed down from generation to generation. This will result in betterquality production that can be used for personal consumption or marketing.